Biodemographic Analysis of Factors Related to Perinatal Mortality in Portugal (1988-2011) - Vicente Fuster (Hindawi Limited, 2016)
Background. The purpose of this paper is to determine the relative mortality risks at delivery and during the first week of life with regard to maternal and foetal characteristics. Methods. Yearly individual digital records on live births and early neonatal mortality were used to infer the possible factors involved in perinatal deaths. Results. The results show that the number of births per year declined with time throughout the period studied. At the same time, rates decreased in 66.4% for stillbirths and in 70.2% for early neonatal mortality. Logistic regressions modelled the interaction of the two mortality indicators and covariables such as birth weight and the duration of gestation. Conclusions. This research provides a first biodemographic approach to the knowledge of factors influencing perinatal mortality in Portugal based on a set of foetal and maternal variables. Although the magnitude of the different perinatal mortality rates may be affected by the criteria used for selecting cases (multiple-singletons; minimum birth weight or minimum duration of gestation), one of the conclusions of the present analysis is that the relationship among the maternal and foetal variables that determine the relative risk remains unaltered. Certain resemblance with the factors determining negative birth outcomes in Spain is appreciated.